Economic growth, efficiency and environmental elasticity for the G7 countries. (July 2019) - Bampatsou, Christina; Halkos, George
Abstract: In this study the non-parametric method of Data Envelopment Analysis (DEA) is applied to determine the technical efficiency (TE) index of the G7 countries, when variable returns to scale (VRS) hold for the entire period under consideration (1993–2016). As inputs labor and capital are used while we utilize GDP as output. In the second stage of our analysis the DEA bootstrap approach along the lines of Simar and Wilson (2007) is applied to deal with the disadvantages of a non-parametric DEA set up. Through this procedure we investigate the relationship between the efficiency evaluation of DMUs as calculated by the DEA method, in the first stage of our analysis, and the variables of arable land, total greenhouse gas emissions and total primary energy consumption. In addition, for these variables and through the estimated regression coefficients, elasticities and marginal effects of both TE and GDP index are calculated. Highlights: The Technical Efficiency index of G-7 countries is determined through the DEA method. The DEA bootstrap approach is applied to deal with the problem of bias and inconsistency. Estimation of the Tobit, truncated and Simar-Wilson bootstrapped truncated regression models. Estimation of long-run elasticities of TE and GDP with respect to environmental variables. Marginal effects of environmental factors to both TE and GDP index are calculated.